The Effects of One-Time Laughter Therapy on Stress Response, School Life Adjustment and Ego-resilience of Women College Students - Cha Mi-Youn; Kim Ji Suk (Journal of Management Practices, Humanities and Social Sciences, 2018)
This research aims to develop and assess the effectiveness of a one-time laughter therapy program for college nursing students. It intends to investigated the effectiveness of this program on their stress response, school life adjustment and ego-resilience. It is a quasi-experimental research of nonequivalent control group pre/post test design. 33 people each of an experimental group and a control group participated in this research (n = 66). After operating the one-time laughter therapy on two groups, this study measured their stress response, school life adjustment and ego-resilience during the same period. The results demonstrated that their stress response was p = .040 and their school life adjustment was p = .012, which meant that the one-time laughter therapy exerted a significant influence on them. The findings suggest that one-time laughter therapy can help college nursing students relieve their stress and adjust to their school life well. This program also enhanced the ego-resilience of the students. Based on the results, it is recommended that the laughter therapy program should be introduced and operated consistently in nursing colleges to regulate the stress response and school life adjustment and promote the health of nursing students.